Hybrid Carbon Fibers/Carbon Nanotubes Structures for Next Generation Polymeric Composites - M. Al-Haik; C. C. Luhrs; M. M. Reda Taha; A. K. Roy; L. Dai; J. Phillips; S. Doorn (Journal of Nanotechnology)
Pitch-based carbon fibers are commonly used to produce polymeric carbon fiber structural composites. Several investigations have reported different methods for dispersing and subsequently aligning carbon nanotubes (CNTs) as a filler to reinforce polymer matrix. The significant difficulty in dispersing CNTs suggested the controlled-growth of CNTs on surfaces where they are needed. Here we compare between two techniques for depositing the catalyst iron used toward growing CNTs on pitch-based carbon fiber surfaces. Electrochemical deposition of iron using pulse voltametry is compared to DC magnetron iron sputtering. Carbon nanostructures growth was performed using a thermal CVD system. Characterization for comparison between both techniques was compared via SEM, TEM, and Raman spectroscopy analysis. It is shown that while both techniques were successful to grow CNTs on the carbon fiber surfaces, iron sputtering technique was capable of producing more uniform distribution of iron catalyst and thus multiwall carbon nanotubes (MWCNTs) compared to MWCNTs grown using the electrochemical deposition of iron.